Strategic management of edupark tourism school development and educational tourism - Aprilla, Indri Ribbut; Khamidi , Amrozi; Haq , Mohammad Syahidul; Sholeh , Muhammad; Amalia , Kaniati (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
This research is motivated by the increasing need for learning innovation that is relevant to the demands of the 21st century as well as local government policies that encourage the strengthening of educational tourism in schools. Sekolah wisata is seen as an effective, contextual learning model, and has the potential to strengthen the profile of Pancasila students. This study aims to analyze the strategic planning, implementation, and evaluation of Tourism school programs in two elementary schools in the city of Surabaya and formulate a strategic management-based development model that can be replicated. The research method used a multi-site qualitative approach involving two schools as a sample. Data were collected through in-depth interviews, observations, and document studies, while analysis was performed using interactive models. The results showed that the success of Tourism schools was supported by visionary leadership, teacher creativity, strong external collaboration, and regional policy support such as restrictions on out-of-town study tours and Adiwiyata programs. However, the evaluation process is still administrative and has not used standard instruments so it has not been able to describe the impact of the program comprehensively. The conclusion of this study concludes the need for the preparation of a Strategic Evaluation Matrix for tourism schools and recommends local governments to establish standardized performance indicators to strengthen monitoring, evaluation, and program sustainability.